Applying genomics in heart transplantation. (12th February 2018) - Keating, Brendan J.; Pereira, Alexandre C.; Snyder, Michael; Piening, Brian D.
Summary: While advances in patient care and immunosuppressive pharmacotherapies have increased the lifespan of heart allograft recipients, there are still significant comorbidities post‐transplantation and 5‐year survival rates are still significant, at approximately 70%. The last decade has seen massive strides in genomics and other omics fields, including transcriptomics, with many of these advances now starting to impact heart transplant clinical care. This review summarizes a number of the key advances in genomics which are relevant for heart transplant outcomes, and we highlight the translational potential that such knowledge may bring to patient care within the next decade.